Pengukuran Kualitas Website Program Studi Sistem Informasi Universitas Brawijaya menggunakan Metode WebQual 4.0 dan Importance and Performance Analysis - Aditya Evan Yudistira; Buce Trias Hanggara; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
In the Information System Study Program of the Faculty of Computer Science, Universitas Brawijaya, website is one of the facilities developed by information system study program in providing information to their students. In order to maintain the quality of education by providing qualified facilities, and part of managing quality assurance, it is necessary to measure the quality of the website that has never been done before, this measurement is carried out using the WebQual 4.0 method in which there are three dimensions, the dimensions are information quality, service interaction quality , and usability, this method is carried out to find out whether the current performance of the website meets the interests or expectations of users. In supporting the measurement, the IPA method, conformity analysis and gap analysis are also used. The IPA analysis is carried out to find out which attributes on which dimensions require more attention to be prioritized for improvement. The results of the analysis conducted on data taken from 99 respondents showed that there were no attribute included in the first quadrant (high priority) but there were seven attributes included in the third quadrant (low priority) so these attributes that must be considered even with low priority. Other attributes do not have priority in improvement because they already have good performance and should be maintained for quality or even those that have excessive performance.